IMPLEMENTASI PENYUSUNAN LAPORAN PENYELENGGARAAN PEMERINTAHAN DAERAH (LPPD) DALAM PELAKSANAAN PEMBANGUNAN DI KOTA METRO - Elip Heldan; Malik Malik; Ade Thiya Delisa (Universitas Bandar Lampung (UBL), 2020)
The problems in this study are: (1) There are still a lot of each Regional Apparatus Organization (OPD) that does not pay enough attention in submitting their performance data reports when it comes to the drafting team. (2) Data for filling in Key Performance Indicators (IKK) from each Regional Apparatus Organization (OPD) still contains data that is not filled in or does not match.This study uses a descriptive research method with a qualitative approach. This aims to determine the events or facts, phenomena that occur during descriptive research with data collection techniques in the form of interviews, observation and documentation using research instruments as interview guides to several informants who have been determined and the main data source in this study using Snowball Sampling.The results showed that the implementation of the compilation of regional government administration reports (LPPD) in the implementation of development in the city of Metro has been running based on the stipulated government regulations. The supporting factors for the Implementation of Regional Government Administration Report Preparation (LPPD) in the Implementation of Development in Metro City come from communication and resources, and the inhibiting factors come from the disposition and structure of the bureaucracy.